1989
DOI: 10.1111/j.1365-3016.1989.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Low blood manganese levels in Liverpool children with Perthes' disease

Abstract: The aetiology of Perthes' disease of the hip, avascular necrosis of the head of the femur, is unknown. Children with the disease have a generalised abnormality of growth. A similar disproportionate growth is found in chicks given a diet deficient in manganese. In Liverpool, which has the highest incidence of Perthes' disease reported anywhere in the world, children with the disease were shown to have lower blood manganese levels than controls. This is evidence that manganese deficiency around the time of birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Several reports have suggested that environmental factors within a socially-deprived population may play a role in the development of Perthes' disease. Hall et al 16 showed that children in Liverpool with…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that environmental factors within a socially-deprived population may play a role in the development of Perthes' disease. Hall et al 16 showed that children in Liverpool with…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence rates seen in Liverpool may therefore reflect the fact that the city is the most deprived English local authority region, as documented in the 2004, 2007 and 2010 English Indices of Deprivation. Suggested aetiological factors include exposure to tobacco smoke,12 hyperactivity,13 clotting disorders14 and dietary deficiencies,15 but none have been satisfactorily established.…”
Section: Introductionmentioning
confidence: 99%
“…The patients are below average in stature, have retarded skeletal maturation, and skeletal disproportion 23 Hall and colleagues4 noted that similar disproportionate growth is found in chickens suffering from trace metal deficiency, and found low serum manganese concentrations in their patients, but this has not been confirmed 5. Glueck and colleagues6 reported that patients had a deficiency of antithrombin factors, but this is unproven 7.…”
mentioning
confidence: 99%